An analysis of end-of-life vehicle policy implementation in Malaysia from the perspectives of laws and public perception - Zambri Harun,; Wan Muhammad Syahmi Wan Mustafa,; Dzuraidah Abd Wahab,; Mohd Radzi Abu Mansor,; Nizaroyani Saibani,; Rozmi Ismail,; Hasani Mohd. Ali,; Noor Azuan Hashim,; Siti Maisarah Mohd Paisal, (Penerbit Universiti Kebangsaan Malaysia, 2021)
End-of-life vehicles (ELV) policy implementation has long been a hotly debated issue in Malaysia. Vehicles that have become ELVs should be disposed of accordingly to prevent environmental pollution and also for the purpose of recycling useful materials, particularly metals. The automotive industry affects the earth environment through greenhouse gas emissions such as air-conditioning gas (CFC/HFC) which will increase global warming and uncontrolled use of raw materials. Even poorly managed ELV waste will cause gas emissions and toxic substances to be released to the environment. To reduce this problem, the implementation of an ELV policy should be seriously considered. In order to have a successful implementation of the ELV policy, support from the public is essential. Thus, this study aims to understand the ELV related laws and their implementation in the neighbouring countries and to ascertain public perception on ELV implementation in Malaysia. The study involves literature search on implemented ELV laws in the neighbouring countries and a survey involving 58 respondents. Results from the survey were analysed using SPSS. This paper presents and discusses the findings from the study. The study indicates that the level of public awareness and acceptance of ELV implementation are quite low. In general, it can be concluded that the implementation of ELV in Malaysia needs to be carefully studied before it is implemented in order to ensure acceptance from the public.